Occurrence of Chordoid Glioma With Sodium Ion Metabolism Disorder 5 Years After Meningioma Surgery and Whole-Exome Sequencing: A Case Report and Literature Review - Zhang, Mei; Xu, Baofeng; Li, Chang; Liu, Ziwei; Gao, Yuanyuan; Song, Yuming; Liu, Rui (Frontiers in Genetics, 2021)
Chordoid glioma (CG), a rare slow-growing brain tumor, mainly occurs in the region of the third ventricle. Although its degree of malignancy is relatively low, its clinical prognosis is poor due to obscure clinical manifestations and the particular growing position. Currently, gross total resection is the best available method for treatment of CG. However, the tumor is located in the deep structure of the brain and close to neurovascular structure so it is difficult to remove completely. We report a case of right frontal parietal fibrous meningioma with CG of the third ventricle detected during postoperative 5-year follow-up. Different from previous reports, in the present case, CG merged with another solid brain tumor, and combined with peri and postoperative sodium ion metabolism disorder. The occurrence of two primary intracranial tumors without a history of radiation therapy or genetic disease is a very rare event. Whole-exome sequencing showed that the meningioma shared 25 gene mutations with CG. In addition, the PRKCAD436H CG marker gene mutation also existed in this patient. In this article, we reviewed the latest literature on this rare brain tumor, summarized its clinical manifestations, imaging and pathological characteristics, and discussed the mechanism related to its occurrence and the reasons for sodium ion disorder.